PEMIKIRAN PENDIDIKAN SPIRITUAL SYAIKH 'ABD AL-QADIR AL-JILANIY - Badrudin, Badrudin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
The Principles of Islam requirehuman to maintain and improve their moral values BuT in fact, many Moslems face problems of moral deteriora tion, crisis of beliefs, and moral decadence that happenin all aspects of life. This moral deterioration is often associated by the experts of education with the failure of educat ion. The failure of education relates to the education system that has various components that affect each other. The elements needed in the education system are the goal of education , educators, students, tool s, and natural surroundings. The results of this study indicate that the essence of spiritual learning obligations according to Syaikh 'Abd al-Qadir al-Jilaniy is araising the total of truth towards Allah SWT's path. The aims of the learning areto implement knowledge and clean the heart (tazkiyyah al-nafs) from worldly characters and the lust of dirtiness to ma'rifatullah. Spiritual educators are those who practice the law of Allah, clean the heart and guide students to the safety of life in the Hereafter . Learners constantly face Allah and obey Him, do not meet the call besides Allah, listen to the call of Allah and implement everything stated in the Qur Â·an and the Prophet tradition. Teaching method used is the method of mau'izhah, sima', ahwal , and muhasabah fial-nafs (introspection). Educational materials are based on the basics of spiritual education in the Qur'an, the Prothet tradition. and the opinion of Muslim religious leaders who have noble characters and integrate science. Moral education is the core of Islamic education. The implications of the spiritual educational thought of Syaikh 'Abd al-Qadir al-Jilaniy toward the reality of Islamic education in Indonesia is the emphasis of moral education that leads to a balance relationship between the exoteric and esoteric aspects of the learning process.